Development of Infusion Device Analyzer Equipped with Occlusion Detection and a Real-Time Parameters Monitoring on Computer System - Anita Miftahul Maghfiroh; Nina Havilda; Sima Das (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
Medical infusion device provides drugs or fluids directly through a blood vessel. However, the occurrence of occlusion in the infusion device causes the incoming drug fluid does not to flow constantly, and pressure is formed on the infusion tube. When an infusion device has been used for a long time, there will be a change in the precision of the flow and pressure values. Furthermore, a calibration process must be carried out at least once a year. This research aims to design an infusion device analyzer which able to show parameters in a graphic equipped with occlusion parameters and Bluetooth communication in real-time to the computer unit. This study uses a solenoid valve for pressure simulation. The allowable occlusion limit is <20 Psi. The SKU 237545 sensor detects the water pressure that is blocked by the solenoid valve. Then the data will be displayed on the Parallax data acquisitions using Bluetooth communication. The Parallax data acquisitions will display real-time occlusion data, data averages, instant values, and graphs. The results of the IDA design, when tested using the Syringe Pump TOP 5300, obtained an average of 0.68 Psi. Meanwhile, when the IDA design was tested using the Infusion Pump 3300, it brought 0.73 Psi. Furthermore, it showed that the occlusion parameter was compared with the Fluke IDA 4, a mean error was 0.7 Psi. Therefore, it can be concluded that this IDA design can be used for calibration to see the feasibility of an infusion pump or syringe pump.